Unilingual Versus Bilingual Education System : A Political Economy Analysis - Javier Ortega; Thomas P. Tangerås (Institute for the Study of Labor (IZA), 2004)
We consider an economy with two language groups, where only agents who share a language can produce together. Schooling enhances the productivity of students and may modify their language endowment. Under a unilingual system, the language of the politically dominant group is the only language of instruction, and the members of the politically dominated group who attend school shift language. Instead, under a bilingual system, the members of the dominated group who attend school become bilingual. The dominant group chooses the education system, and then individuals decide whether to attend school. While agents do not get utility from speaking their own language, we show that a language conflict of the expected type endogenously arises in the choice between a unilingual and a bilingual system. Democracy (majority rule) always leads to the implementation of the socially optimal education system, while the unilingual system is too often implemented under minority rule. In the presence of productivity spillovers, there may be unanimity for unilingualism, even if this system is assumed to be technologically inferior. The model is consistent with evidence from Finland in 1919 and France in 1863, showing that the choice of bilingualism in education may not be related to the size of language groups.
Keywords: I2; J15; 330; education; language policies; skills; minorities; Bildungswesen; Mehrsprachigkeit; Minderheit; Public Choice; Theorie